Fully Distributed Event-Triggered Security Control for DC Microgrids Subject to DoS Attacks - Xiao, Feng; Liu, Yu; Zhang, Xiaodan; Wei, Bo (IEEE transactions on smart grid, 2025)
As the application of distributed DC microgrids becomes more and more widespread, their voltage restoration and current sharing that cannot be guaranteed simultaneously due to droop control have received a lot of attention. In this paper, we propose a new adaptive safety control strategy with an event-triggering mechanism to reduce the communication burden. The current sharing of the distributed generation units is guaranteed while bus voltage deviations are eliminated. The control objectives are well achieved even under DoS attacks. Moreover, the controller and the triggering mechanism are designed to be scalable without the bus voltage sampling and any global information. The stability of the control system is proved by the Lyapunov theory, and Zeno behavior is also strictly ruled out. Finally, the simulation results illustrate the validity of the proposed approach.